2012
DOI: 10.3389/fonc.2012.00098
|View full text |Cite
|
Sign up to set email alerts
|

The strategy for enhancing temozolomide against malignant glioma

Abstract: A combined therapy of the alkylating agent temozolomide (TMZ) and radiotherapy is standard treatment, and it improves the survival of patients with newly diagnosed glioblastoma (GBM). The DNA repair enzyme O6-methylguanine-DNA methyltransferase (MGMT) removes the most cytotoxic lesions generated by TMZ, O6-methylguanine, establishing MGMT as one of the most important DNA repair mechanisms of TMZ-induced DNA damage. Thus, the expression of MGMT, its activity, and its promoter methylation status are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 38 publications
(46 reference statements)
0
49
0
Order By: Relevance
“…It has also been reported that Res sensitizes GBM tumor initiating cells to radiotherapy by inhibition of STAT3 axis (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Res sensitizes GBM tumor initiating cells to radiotherapy by inhibition of STAT3 axis (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Dual targeting of base excision repair and NAD(+) biosynthesis may reverse TMZ resistance in patients with resistant and recurrent GBM (Goellner et al, 2011). Interferon-β (IFN-β), levetiracetam (LEV), resveratrol, and valproic acid (VAP) increase the sensitivity of TMZ through MGMT-dependent or -independent mechanisms (Nakada et al, 2012). Resveratrol, a natural polyphenol, reverses TMZ resistance via an NF-κB-dependent mechanism (Huang et al, 2012).…”
Section: Mechanisms Of Resistance To Temozolomide In Glioblastomasmentioning
confidence: 99%
“…This means that other factors, which are currently not known, are probably involved in GBM resistance. The precise mechanism of cell death triggered by TMZ, is still subject to controversial discussion and studies of the association of TMZ with other drugs indeed revealed a complex array of mechanisms implicated in TMZ cytotoxicity [5]. It has been reported that TMZ through the production of O 6 -methylguanine was inducing apoptosis [6].…”
Section: Introductionmentioning
confidence: 99%